2004
DOI: 10.1289/ehp.6591
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine-disrupting effects of cattle feedlot effluent on an aquatic sentinel species, the fathead minnow.

Abstract: Over the last decade, research has examined the endocrine-disrupting action of various environmental pollutants, including hormones, pharmaceuticals, and surfactants, in sewage treatment plant effluent. Responding to the growth of concentrated animal feeding operations (CAFOs) and the pollutants present in their wastewater (e.g., nutrients, pharmaceuticals, and hormones), the U.S. Environmental Protection Agency developed a new rule that tightens the regulation of CAFOs. In this study, we collected wild fathea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
191
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(198 citation statements)
references
References 40 publications
3
191
2
2
Order By: Relevance
“…Some of these chemicals have been shown to alter sexual programming and reduce reproductive fitness in wild fish at environmentally relevant exposure concentrations (31,52,53). Additive effects have been shown for EDCs acting as estrogen receptor agonists (54), but less consideration has been given to the combined effects of exposure to EDCs with other modes of action, including modulators of other steroid hormone receptors (e.g., androgen receptor agonists or antagonists) and disruptors of hormone synthesis and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these chemicals have been shown to alter sexual programming and reduce reproductive fitness in wild fish at environmentally relevant exposure concentrations (31,52,53). Additive effects have been shown for EDCs acting as estrogen receptor agonists (54), but less consideration has been given to the combined effects of exposure to EDCs with other modes of action, including modulators of other steroid hormone receptors (e.g., androgen receptor agonists or antagonists) and disruptors of hormone synthesis and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…18 Previous studies also reported that there is a connection between exposure of androgens and masculinization of fish. 48,49 Since there have been no reported PNEC values for androgens, glucocorticoids and progestagens, proper risk assessment could not be made. Therefore, control measures should be applied to further remove these steroids in the final effluents in order to reduce potential risks to aquatic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing number of reports on intersex organisms found in global aquatic ecosystems has raised concerns regarding the occurrence and persistence of steroid hormones in the environment (Safe, 2004;Wise et al, 2011). Several studies have reported the masculinization of freshwater wildlife exposed to androgens in polluted rivers (Howell et al, 1980;Bortone et al, 1989;Parks et al, 2001;Orlando et al, 2004). Furthermore, steroids were identified as pheromones and adversely affect fish behavior even at extremely low concentrations (Kolodziej et al, 2003).…”
Section: Introductionmentioning
confidence: 99%